Afirma Testing in Thyroid Nodules with Indeterminate Cytology: A single Medical Institute Experience. (28th October 2020) - Yang, Z; Zhang, T; Layfield, L; Esebua, M
Abstract: Introduction/Objective: About 10 to 30% of thyroid fine needle aspiration (FNA) nodules have indeterminate cytology, including Bethesda III, IV, and V. Afirma Gene Expression Classifier (GEC) measuring the expression of 167 mRNA was designed to classify the indeterminate thyroid nodules into benign and suspicious categories. This study aimed to evaluate the clinical performance of the Afirma GEC testing in these indeterminate thyroid lesions. Methods: Medical records of patients with indeterminate thyroid FNA results and corresponding Afirma GEC results from November 2012 to December 2019 were retrieved. Subsequent surgical follow-up results were obtained. GEC results were compared to the histologic diagnoses. Results: 1. There were 77 cases with indeterminate thyroid FNA results. Cytology diagnosis included 67 Bethesda III and 10 Bethesda IV. Afirma GEC results were benign for 41 cases (53%), suspicious for 32 cases (42%), and non- diagnostic for 4 cases (5%). Twenty seven of 32 cases (84%) with suspicious GEC results had surgical follow-up which revealed 12 malignant and 15 benign histologic diagnoses. Only 11 of 41 cases (27%) with benign GEC results had surgery which showed 8 benign and 3 malignant diagnoses. Based on the data, the sensitivity of this test is 80% and specificity is 65%. Positive predictive value (PPV) is 44% and negative predictive value (NPV) is 73%. The false positive cases include 5 Hurthle cell adenoma, 4 nodular hyperplasia, 3 follicular adenoma, 2 Noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFPT), and 1 lymphocytic thyroiditis. The false negative cases include 2 minimally invasive follicular carcinoma (from same patient) and 1 papillary thyroid carcinoma. Conclusion: 1. We demonstrated in this study that a little more than half of the cases with indeterminate thyroid cytology had negative Afirma GEC results. 2.Afirma test has relatively low specificity (65%) and PPV (44%). The sensitivity (80%) and NPV (73%) is relatively higher but is lower than the values in most literature. This could be due to the fact that majority of the Afirma GEC negative cases in this study did not have surgical follow-up and the sample size is small. 3.Afirma GEC test is a relatively good "rule-out" molecular test for indeterminate thyroid nodules but is not a reliable "rule-in" test due to the low specificity and PPV.